2015
DOI: 10.1053/j.ajkd.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Kidney Function on Risk of Supratherapeutic International Normalized Ratio–Related Hemorrhage in Warfarin Users: A Prospective Cohort Study

Abstract: Background Anticoagulation management is difficult in chronic kidney disease, with frequent supratherapeutic international normalized ratio (INR ≥4) increasing hemorrhagic risk. We evaluated whether the interaction of INR and lower estimated glomerular filtration rate (eGFR) increases hemorrhage risk and whether patients with lower eGFR experience slower anticoagulation reversal. Study Design Prospective cohort study. Setting & Participants Warfarin pharmacogenetics cohort (WPC) (1273 long-term warfarin us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 46 publications
(43 reference statements)
6
40
0
2
Order By: Relevance
“…baseline use not reflecting use at time of the VTE), underdosing in CKD patients (because of concerns about bleeding, and alterations in non‐renal clearance), or difficulties in achieving stable International Normalized Ratios in CKD patients. Whether warfarin would be practical in the primary prevention of VTE in CKD patients would require a randomized controlled trial to determine, and the bleeding risk, which might offset any protective effect, must be taken into account . Our finding related to statin use confirms the results of prior studies , and suggests further study of statins (which do not cause bleeding) for VTE prevention in CKD patients.…”
Section: Discussionsupporting
confidence: 82%
“…baseline use not reflecting use at time of the VTE), underdosing in CKD patients (because of concerns about bleeding, and alterations in non‐renal clearance), or difficulties in achieving stable International Normalized Ratios in CKD patients. Whether warfarin would be practical in the primary prevention of VTE in CKD patients would require a randomized controlled trial to determine, and the bleeding risk, which might offset any protective effect, must be taken into account . Our finding related to statin use confirms the results of prior studies , and suggests further study of statins (which do not cause bleeding) for VTE prevention in CKD patients.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, observational studies have led to doubts about the use of warfarin in this population. 3,4 Only few observational studies have reported eGFR in AF cohorts, and these have generally focused on either the risk of stroke associated with reduced renal function without anticoagulation 5 or the risk of bleeding associated with reduced renal function while on anticoagulation. 3 Data on the risks associated with mildly reduced renal function are sparse.…”
mentioning
confidence: 99%
“…Platelet dysfunction and alterations in the coagulation cascade can complicate the use of anticoagulants in patients with CKD . We have previously shown that patients with CKD have slower rates of INR reversal when presenting with overanticoagulation than do patients with normal renal function . This finding has led us to hypothesize that patients with CKD have a slower rate of carboxylation of clotting factors.…”
Section: Discussionmentioning
confidence: 99%
“…Warfarin is a commonly used oral anticoagulant for treatment of clotting disorders and prevention of AF‐related stroke. Recent evidence suggests that although warfarin is metabolized in the liver, renal function significantly affects warfarin dosing and toxicity . Patients with CKD have a higher frequency of supratherapeutic international normalized ratios (INRs), and the risk of warfarin‐associated hemorrhage is increased in patients with lower eGFRs .…”
mentioning
confidence: 99%